Farm Efficiency and Socioeconomic Determinants of Rain-Fed Rice Production in Myanmar: A Non-Parametric Approach - SAN , Nan Wutyi; ABDLATIF , Ismail; MOHAMED , Zainal Abidin bin (Asian Journal of Empirical Research, 2013)
The rice sector in Myanmar is predominantly for local consumption, maintaining national food security and uplifting the rural economy. The objective of the study is to estimate the value of economic efficiency and its determinant factors on paddy production by across farm sizes. A total sample of 400 rice farm households was randomly collected from main growing areas, in which farms were divided into three strata: small (<2.02 ha), medium farms (2.02-4.05) and large farms (>4.05 ha). Using Data Envelopment Approach, the empirical occurrence of efficiency analysis revealed that the average pure technical efficiency, allocative efficiency, economic efficiency, overall technical efficiency and scale efficiency of small farms were higher than other two farm size groups: medium and large farms size groups; therefore, small farms size groups were more economically benefits. Age of farmers, education level, extension visit, credit, seed replacements and frequency of fertilizer application were major factors affecting on efficiency scores. Policies leading to improving farmer knowledgeable level through provision of Workshops and training programs and helping to small farms by contribution input deliveries such good seeds, certified fertilizers are very important to enhance the achievement of total farms economic goals and increase farm efficiency in the area.